Workplace Violence, its Determinants and Reaction toward it Perceived by Nurses Working in Psychiatric Wards: A Cross-Sectional Study - F Rahmani; H Ebrahimi; E Asghari (Iran University of Medical Sciences, 2015)
Abstract Background & Aim: Workplace violence is considered as one of the important issues in occupational health. This issue in psychiatric ward requires more special attention due to type of patients admitted there and nature of psychiatric disorders. The aim of this study was to determine workplace violence, vulnerable and preventive factors and reaction towards violence perceived by nurses working in psychiatric wards. Material & Methods: In this cross-sectional study, 144 nurses (6 practical, 130 bachelor and 8 masters of nursing) working in psychiatric wards of Razi hospital in Tabriz, Iran were participated using census sampling method. Data gathered with "International Workplace Violence Questionnaire". Data analysis was conducted using descriptive statistics on SPSS v 13. Results: Verbal and physical violence with the frequency of 96.5% and 83.3% respectively, were the most of occurrence and cultural and sexual violence with the frequency of 27.0% and 9.7% were the least of occurrence in the work environment of nurses. Most frequent reaction of nurses to workplace violence was to calm aggressive person (27.8%).Increasing human resources (16.7%), continuing education staff (15.7%), security measures in sectors (14.2%), management guideline for violence (13.7%) and separating judicial patients from other patients (12.8%) were reported main factors to prevent workplace violence. The most common predisposing factors for violence against nurses were low ratio of nurses to patients (12.9%), lack of timely security (10.9%), legal issues of patients (10.3%), inappropriate treatment of staff with patients or their companions (8.9%) and lack of training on how to prevent violence (8.3%). Conclusion: The high prevalence of violence against psychiatric nurses indicates need to upgrade nurses' communication skills, anger management training and reduce the workload of nurses in order to reduce the violence.